MEMBANGUN MORALITAS SENI MELALUI PENDIDIKAN (Building Art Morality through Education) - Nurharini, Atip (KREATIF, 2010)
There is contradiction on art creation breaking the pornography act. ItÃÂ  has the impact at existing argumentation on the form of beauty and badness of an art creation. There are some ideas to give nature asmosphere of the contradiction, just like that art is aesthetic scope finding the nature of beauty and badness values, making creation, and expressing its beauty. on the other hand, morality is ethical scope finding the goodness and badness values. Knowledge is epistemology scope examining the truth and wrongness values. Based on some ideas above, the problems of the research were whether there was morality within art, and whether art morality could be build through education, or vise versa, and also whether there was art that was free of any values except its aesthetic values. This writing tried to discuss those problems and give alternative solutions. It also tried to discuss those problems using religion and philosophy approaches. In any religion perspective, each of human beings will be responsible for his/her deeds, including art creation and expression, at least in morality responsibility. However, it is necessary to know that there is morality within art. Keywords: morality, art, education, aesthetics